Comparing the effects of maternal and paternal incarceration on adult daughters’ and sons’ criminal justice system involvement: a gendered pathways analysis - Burgess-Proctor, Amanda (Criminal justice and behavior, 2016)
This analysis compares the effects of maternal and paternal incarceration on adult daughters' and sons' criminal justice system (CJS) involvement. Data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) are used to examine differences by parent and offspring sex in the effect of parental incarceration on respondents' self-reported arrest, conviction, and incarceration after age 18 (N = 15,587). Net of controls, both maternal and paternal incarceration significantly increase log odds of adult offspring CJS involvement. This effect is especially pronounced for same-sex parent?child dyads, suggesting that the salience of parental incarceration for adult offending outcomes is gendered. In addition, intimate partner abuse and running away are significant predictors of adult CJS involvement for women, but not for men. The results suggest the importance of examining parental incarceration using a gendered, developmental framework such as gendered pathways, as well as the need for gender-responsive correctional programming.